Paraganglioma Mimicking a Pancreatic Neoplasm - Lightfoot, Nicole; Santos, Peter; Nikfarjam, Mehrdad (JOP. Journal of the Pancreas, 2011)
Context Paragangliomas are rare tumours of neural crest origin. Extra-adrenal pancreatic paragangliomas are exceptionally rare. Case report A 66-year-old man with abdominal pain was noted to have a complex pancreatic head and uncinate process mass on imaging. He underwent complete resection by pancreaticoduodenectomy with final pathology confirming a 6 cm paraganglioma without evidence of metastases. On histology the tumour was arising from the retroperitoneum and abutting the pancreas. The patient was disease free at 14-month follow-up. Conclusion Pancreatic paragangliomas represent in many cases the retroperitoneal extension of a paraganglioma into the pancreas rather than a true pancreatic neoplasm. Although generally benign, the risk of malignant transformation justifies aggressive management. Image: CT-PET showing no uptake within the cystic component of the mass.